2006
DOI: 10.1590/s0103-65132006000200010
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de gerenciamento de materiais na construção civil utilizando avaliação multicritério

Abstract: This paper discusses a more structured model for the decision-making process with regard to management material process, through the application of the multicriteria decision aid method as a support in one model. The management material process has assumed great relevance due to its strategic role on reducing costs and pushing up the construction companies' technological and organizational innovation. The basic question to be considered is how the material classification can be done using multiple criteria. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…For Gomes, González Araya and Carignano (2004), Electre Tri classifies the various alternatives for solving a problem by comparing each potential alternative to a reference alternative. As examples of application of Electre Tri in different environments, and of its relationship with other approaches, one can find Brito, Almeida and Mota (2010), Szajubok, Alencar and Almeida (2006), Campos and Almeida (2010), Gomes and Costa (2008), Doumpos and Zopounidis (2002), Costa, Santafé Júnior and Haddad (2007), Neves and Costa (2010) and Mousseau, Slowinski and Zielniewicz (2000); among others.…”
Section: The Electre Tri Multicriteria Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Gomes, González Araya and Carignano (2004), Electre Tri classifies the various alternatives for solving a problem by comparing each potential alternative to a reference alternative. As examples of application of Electre Tri in different environments, and of its relationship with other approaches, one can find Brito, Almeida and Mota (2010), Szajubok, Alencar and Almeida (2006), Campos and Almeida (2010), Gomes and Costa (2008), Doumpos and Zopounidis (2002), Costa, Santafé Júnior and Haddad (2007), Neves and Costa (2010) and Mousseau, Slowinski and Zielniewicz (2000); among others.…”
Section: The Electre Tri Multicriteria Methodsmentioning
confidence: 99%
“…It is suggested that the initial results are obtained considering a cutoff λ = 0.5 as a first estimate, and then subsequently increasing the cutoff for support the sensitivity analysis step. Readers can consult Szajubok, Alencar and Almeida (2006) for more information about this procedure.…”
Section: Electre Tri Executionmentioning
confidence: 99%
“…As a result, the formal housing market ends up excluding the low-income population due to the high costs of construction materials and labor, loan interest rates, and contractor profits [34]. Throughout the national territory, resource acquisition for MCMV residential projects may be affected by limitations related to logistics or price fluctuations of raw materials and labor [35].…”
Section: National System Of Costs and Indexes For Civil Construction ...mentioning
confidence: 99%
“…Em relação ao contexto da construção civil observa-se na literatura alguns trabalhos envolvendo a aplicação de métodos multicritério de apoio à decisão. Szajubok et al (2006) propõem um modelo estruturado para o gerenciamento de materiais na construção civil baseado no método multicritério ELECTRE TRI. Mota et al (2009) apresentam um modelo multicritério para auxiliar os gestores na priorização de atividades de projeto.…”
Section: Abordagem Multicritério De Apoio à Decisãounclassified